Roles of maternal effects and nuclear genetic composition change across the life cycle of crop–wild hybrids1. Issue 7 (1st July 2014) - Alexander, Helen M.; Emry, D. Jason; Pace, Brian A.; Kost, Matthew A.; Sparks, Kathryn A.; Mercer, Kristin L.
Abstract : Premise of the study: The fitness of an offspring may depend on its nuclear genetic composition (via both parental genotypes) as well as on genetic maternal effects (via only the maternal parent). Understanding the relative importance of these two genetic factors is particularly important for research on crop–wild hybridization, since traits with important genetic maternal effects (e.g., seed size) often differ among crops and their relatives. We hypothesized that the effects of these genetic factors on fitness components would change across the life cycle of hybrids. Methods: We followed seed, plant size, and reproductive traits in field experiments with wild and four crop–wild hybrids of sunflower ( Helianthus annuus ), which differed in nuclear genetic composition and maternal parent (wild or F1 hybrid). Key results: We identified strong genetic maternal effects for early life cycle characteristics, with seeds produced on an F1 mother having premature germination, negligible seed dormancy, and greater seedling size. Increased percentages of crop alleles also increased premature germination and reduced dormancy in seeds produced on a wild mother. For mature plants, nuclear genetic composition dominated: greater percentages of crop alleles reduced height, branching, and fecundity. Conclusions: Particular backcrosses between hybrids and wilds may differentially facilitate movement of crop alleles into wild populations due to their specific features. For example, backcross seeds produced on wild mothers can persist in the seed bank, illustrating the importance of genetic maternal effects, whereas backcross individuals with either wild or F1 mothers have high fecundity, resulting from their wild‐like nuclear genetic composition.